Children's recognition of emotions from vocal cues. (6th June 2012) - Sauter, Disa A.; Panattoni, Charlotte; Happé, Francesca
<x xml:space="preserve">Abstract</x> Emotional cues contain important information about the intentions and feelings of others. Despite a wealth of research into children's understanding of facial signals of emotions, little research has investigated the developmental trajectory of interpreting affective cues in the voice. In this study, 48 children ranging between 5 and 10 years were tested using forced‐choice tasks with non‐verbal vocalizations and emotionally inflected speech expressing different positive, neutral and negative states. Children as young as 5 years were proficient in interpreting a range of emotional cues from vocal signals. Consistent with previous work, performance was found to improve with age. Furthermore, the two tasks, examining recognition of non‐verbal vocalizations and emotionally inflected speech, respectively, were sensitive to individual differences, with high correspondence of performance across the tasks. From this demonstration of children's ability to recognize emotions from vocal stimuli, we also conclude that this auditory emotion recognition task is suitable for a wide age range of children, providing a novel, empirical way to investigate children's affect recognition skills.